2017
DOI: 10.21093/di.v17i2.850
|View full text |Cite
|
Sign up to set email alerts
|

A Facilitating Effective Teaching through Learning Based on Learning Styles and Ways of Thinking

Abstract: The study deals with learning styles and ways of thinking in facilitating effective teaching. The objective of this study was to investigate the relationship between students' learning style and ways of thinking toward effective teaching. This study was conducted by using correlational design. The population of the study were 360 university students of English education academic year 2015/2016 in State University of Medan. The samples were 82 university students selected by using random sampling. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The result of this study implies that VAK learning model can be an alternative to improve the students' writing skill. In addition, another research finding which also supports this research finding is a research conducted by Ginting (2017). He demonstrated that learning styles (Visual, Auditory, and Kinesthetic) and ways of thinking contribute to effective teaching.…”
Section: The Students' English Abilitysupporting
confidence: 67%
See 1 more Smart Citation
“…The result of this study implies that VAK learning model can be an alternative to improve the students' writing skill. In addition, another research finding which also supports this research finding is a research conducted by Ginting (2017). He demonstrated that learning styles (Visual, Auditory, and Kinesthetic) and ways of thinking contribute to effective teaching.…”
Section: The Students' English Abilitysupporting
confidence: 67%
“…In addition, Ramdian, Chayono & Suryati (2019) who found that the VAK learning model succeeded in helping the students to improve their writing' achievement. Ginting (2017) demonstrated that learning styles (Visual, Auditory, and Kinesthetic) and ways of thinking contribute to effective teaching. Hardina and Suyata (2018), on other hand, conducted that the VAK model is effective in learning of summary writing.…”
Section: Introductionmentioning
confidence: 99%
“…Reading is a great source of language learning: language can be acquired from reading as opposed to study directly (Pollard, 2008). Reading or writing is in preference to remember particular information (Ginting, 2017). Reading skill plays a very significant role in someone's life.…”
Section: A Introductionmentioning
confidence: 99%
“…It is not possible to have an objectively "optimal" theory, against which educators can compare the ones developed by themselves (see also Hlebowitsh, 2012, p. 3). As Zeichner & Liston (2013) mentioned there are many inceptions of how teaching could be effective (see also Shukla, Dosaya, Nirban, & Vavilala, 2020;Oder & Eisenschmidt, 2018;Ginting, 2017).…”
Section: Discussionmentioning
confidence: 99%